2005
DOI: 10.1007/s10750-005-4463-0
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity and Structure of Macroinvertebrate Communities Along a Small Permanent Salinity Gradient (Meurthe River, France)

Abstract: Changes in the macroinvertebrate community were investigated over 10 months at four sites along a 19 km salinity gradient (0.21-2.60 g l )1 ) in a sixth-order stream, the Meurthe River, northeastern France. Abiotic characteristics other than salinity were similar between the sites. Macroinvertebrate taxonomic richness decreased by 30% downstream of the 1.4 g l )1 sites while diversity, evenness or total abundance of taxa did not change along the gradient. In terms of functioning, a slight change in relative ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
100
1
8

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(130 citation statements)
references
References 34 publications
21
100
1
8
Order By: Relevance
“…Their main vector of intercontinental dispersal is ballast water Nehring 2002), which acts as a strong filter in favour of species with high salinity tolerances. This is, again, consistent with Piscart et al (2005Piscart et al ( , 2011, who also found higher tolerance levels for nonnative species from outside Eurasia.…”
supporting
confidence: 89%
“…Their main vector of intercontinental dispersal is ballast water Nehring 2002), which acts as a strong filter in favour of species with high salinity tolerances. This is, again, consistent with Piscart et al (2005Piscart et al ( , 2011, who also found higher tolerance levels for nonnative species from outside Eurasia.…”
supporting
confidence: 89%
“…The results of correspondence analysis indicated that salinity was the most important environmental variable responsible for community composition among different study sites, as occurs in other studies on coastal (Arnold & Ormerod 1997, Frisch et al 2006 or inland (Boronat et al 2001, Piscart et al 2005) aquatic ecosystems where a salinity gradient exists. In our results, brackish water sites supported a higher abundance of Gastropoda, Chironomidae and Crustacea while Ephemeroptera, Coleoptera and Heteroptera more sensitive to salinity (Williams & Williams 1998, Hart et al 1991 were almost excluded from these habitats.…”
Section: Discussionsupporting
confidence: 70%
“…Finally, future global change will also consist of an increase in the frequency of invasive species. This problem has been widely discussed for surface aquatic systems, both lakes (Gurevitch and Padilla, 2004;Nalepa et al, 2009) and rivers (Dukes and Mooney, 1999;Piscart et al, 2005Piscart et al, , 2010Piscart et al, , 2011Werner and Rothhaupt, 2007;Strayer, 2010;Labat et al, in press). For the hyporheic zone, the occurrence of invasive species is not yet documented even if some invasive isopods and amphipods were already observed (C. Piscart, personal communication).…”
Section: Introductionmentioning
confidence: 99%